121k views
4 votes
Please help and thank you

Please help and thank you-example-1

1 Answer

0 votes

Answer:

D. The equation represents an arithmetic sequence because the successive y-values have a common difference of 6.

Explanation:

y = 6x - 1

f(n) = 6n - 1

f(n + 1) = 6(n + 1) - 1 = 6n + 6 - 1 = 6n + 5

f(n + 1) - f(n) = (6n + 5) - (6n - 1) = 6n + 5 - 6n + 1 = 6 = constant

User The Lazy DBA
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.